ANALYTIC HIERARCHY PROCESS BERBASIS TRIANGULAR INTUITIONISTIC FUZZY NUMBER UNTUK PEMILIHAN SUPPLIER BAHAN KONSTRUKSI TOWER - Novi Hanifatul Ula (MATHunesa: Jurnal Ilmiah Matematika, 2021)
Supplier selection is the process of finding the right supplier, at the right price, at the right time, in the right quantity, and with the right quality. However, it is not easy to identify a good supplier because it requires the fulfillment of several predetermined criteria. In the midst of the Covid-19 pandemic, it has had an impact on carrying out all activities online, for example in work and education. Therefore, the internet today is very influential on everyday life. Thus causing many areas that are still not reached by the internet requires to be able to meet these needs. One way to reach the internet is to build a tower in the area. For this reason, it is necessary to select the right supplier of tower construction materials, at the right price, at the right time, in the right quantity, and with the right quality in tower construction. The purpose of this article is the selection of suppliers of tower construction materials with several predetermined criteria. The method used in this research is Analytic Hierarchy process (AHP) based on Triangular Intuitionistic fuzzy number (TIFN). The Analytic Hierarchy process (AHP) is an effective approach to dealing with multi-criteria decision problems. From these calculations, the best supplier ranking of tower construction materials is vendor B with an overall priority score for the alternative 0.336309 then for the second and third ranked suppliers, respectively, vendor A and vendor C with the overall priority score for the alternative 0.333114 and 0.330577. Keywords: Supplier selection; Analytic Hierarchy process (AHP); Triangular Intuitionistic fuzzy number (TIFN).